Estudio del perfil del visitante del bosque protector "Cascada de Peguche", Otavalo " Imbabura " Ecuador - Lomas, Rolando; Trujillo, Carmen; Moncada, José Alí (Tierra Infinita, 2015)
This research work was aimed at the study of the profile the Cascade Visitor Peguche to propose alternatives for sustainable management and enhance community tourism of the sector. It was determined: a) the typology as age, education, occupation, income level, source and transfer visitors; b) characterization of the visit: frequency, time and reason for the visit, companions, and activities; c) site assessment regarding safety, cleaning, maintenance, care provided, preferences and importance of the place; d) expectations of the visitor; and e) satisfaction. Research descriptive field was used by structured surveys to 120 visitors, selected as representative, stratified random, following a direct and selective observation, during the months of August and September, holiday dates and festivities Yamor Otavalo. The results show that the majority of tourists are domestic, aged 15 to 30 years, graduates and professionals, visit the waterfall several times a year for recreation and relaxation, stay three hours and frequent in family groups and friends; value the attention of the community, like to the woods and want to know about its different uses and ethnobotany, history of the place, getting the information in interpretive signs & tours would support reforestation, avoided the use of plastic in the protected forest and express a very good level of satisfaction. The area is a place of cultural, historical and natural importance, turned into a tourist attraction in the province of Imbabura and country.